Normoxic stabilization of hypoxia-inducible factor-1alpha by modulation of the labile iron pool in differentiating U937 macrophages: effect of natural resistance-associated macrophage protein 1. - Knowles, H; Mole, D; Ratcliffe, P; Harris, A (2006)
Hypoxia-inducible factor (HIF) is a transcription factor with major roles in many cellular and systemic responses to hypoxia. Activation of HIF pathways under hypoxia is mediated by suppression of the Fe(2+)- and O(2)-dependent HIF hydroxylase enzymes that normally inactivate HIFalpha subunits. Mechanisms underlying induction of HIF in normoxic conditions are less clearly understood. In human cancers, infiltrating macrophages show up-regulation of HIF and it has recently been shown that normoxic expression of HIF-1alpha is essential for macrophage function. Here, we report studies of HIF-1alpha induction following phorbol-12-myristate 13-acetate (PMA)-induced differentiation of monocytic U937 and THP1 cells. HIF-1alpha was markedly up-regulated under normoxia in this setting and this involved failure of HIF-1alpha prolyl hydroxylation despite the presence of O(2). Fluorescence measurements showed that differentiation was associated with marked reduction of the labile iron pool. Both the reduction in labile iron pool and the up-regulation of HIF-1alpha were suppressed by RNA interference-mediated down-regulation of the iron transporter natural resistance-associated macrophage protein 1. Up-regulation of HIF-1alpha following PMA-induced differentiation was also abolished by addition of Fe(2+) or ascorbate. These results indicate that physiologic changes in macrophage iron metabolism have an important effect on HIF hydroxylase pathways and suggest means by which the system could be manipulated for therapeutic benefit.